Planning in the spirit of Deleuze and Guattari? Considering community-based food projects in the United States and Mexico. Issue 4 (21st April 2017) - Purcell, Mark; Born, Branden
ABSTRACT: In this article we argue that planning theory and practice should engage more with the normative political vision of Gilles Deleuze and Félix Guattari. They reject the transcendent authority of the State and arguably by extension, planning. As planners we should be concerned: need we reconceptualize, or abandon the planning project? We outline their vision, highlighting key concepts including lines of flight, revolution, the new land, and immanent organization, and use two cases from the United States and Mexico, the Food Commons and Center for Integral Farmer Development in the Mixteca, to show that planning in accordance with Deleuze and Guattari may indeed be possible. We end with questions: is what we describe planning? And what is planning – or what should it be?